Two new species of genus Hesperentomon Price, 1960 (Protura, Hesperentomidae) from Northern China - Bu, Yun; Shrubovych, Julia; Yin, Wen Ying (Zootaxa, 2011)
Two new species of Hesperentomidae are described from northern China. Hesperentomon fopingense sp. nov. is characterized by 16 P-setae on urotergites II–VI, long, slender foretarsal sensilla t-1 and t-2 and a round flap on the inner side of the acrostylus of the female squama genitalis. Hesperentomon dunhuaense sp. nov. is characterized by 12 P-setae on urotergites II–VI, short, slender foretarsal sensilla t-1 and t-2 and a slender flap on outer side of the acrostylus of the female squama genitalis.